1999
DOI: 10.1002/(sici)1098-2264(199905)25:1<46::aid-gcc7>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome abnormalities in ovarian adenocarcinoma: II. prognostic impact of nonrandom chromosome abnormalities in 244 cases

Abstract: In a large series of ovarian carcinomas from 244 patients, 134 cases had chromosome rearrangements. We showed before that the pattern of chromosome breakpoints involved 21 separate chromosome regions nonrandomly and, in 90% of cases with breaks, the breakpoints occurred within 13 commonly involved regions. Log-rank and proportional hazards regression analyses showed that the aggregate presence of a chromosome breakpoint in any of 21 nonrandomly involved regions and breaks in 9 distinct regions (1p1, 1q2, 1p3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…More evident were concordant CGH and SKY aberrations leading to losses distal to 3p21 and gains of 3q and of the region 8q23-q24 arising as a consequence of unbalanced structural rearrangements. In addition, other regions of rearrangement on chromosomes 1, 7, 12, 13, and 19 previously identified by G-banded chromosomal analysis (12,13) were also noted. One-third more structural chromosomal aberrations were identified in the endometrioid tumors than the serous tumors.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…More evident were concordant CGH and SKY aberrations leading to losses distal to 3p21 and gains of 3q and of the region 8q23-q24 arising as a consequence of unbalanced structural rearrangements. In addition, other regions of rearrangement on chromosomes 1, 7, 12, 13, and 19 previously identified by G-banded chromosomal analysis (12,13) were also noted. One-third more structural chromosomal aberrations were identified in the endometrioid tumors than the serous tumors.…”
Section: Discussionmentioning
confidence: 53%
“…Many chromosomal translocations were centromeric or pericentromeric, suggesting the involvement of repetitive centromeric sequences or Alu repeats that may facilitate rearrangements leading to chromosomal imbalance (52). Chromosomal breakage at 1p1* and 3q* occur in ovarian cancer (5,7,11) and confers a poor outcome (13). Ovarian cancer often presents in more than one site or has metastasized at the time of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytogenetic studies and spectral karyotyping have shown chromosome 1 to be frequently involved in rearrangements in ovarian tumors [1][2][3][4][5]. However, specific genes in chromosome 1, of importance for ovarian carcinogenesis, are still not identified.…”
Section: Introductionmentioning
confidence: 99%